The Psychometric Properties of the Polish-Language Version of the Mathematical Resilience Scale - Monika Szczygieł; Marzena Kutt (Journal of Numerical Cognition, 2025)
This study aims to present the psychometric properties of the Polish language version of the Mathematical Resilience Scale (MRS; Kooken et al., 2016), established in a sample of 443 adults. We confirmed the first-order three-factor structure (Value, Struggle, Growth) with the second-order factor (Total Mathematical Resilience) of the MRS and its measurement invariance across gender and field of study and profession. We also confirmed the validity of the scale: negative correlations were found between MRS scores and math anxiety, math avoidance, intellectual helplessness in mathematics; positive correlations were found between MRS scores, mathematical achievement, math learning motivation; no relationship or weak correlations were found between MRS scores, intellectual helplessness in Polish language, Polish language grades obtained in high school. Finally, we observed gender and study and profession differences in some of the MRS scores. However, further research is needed on the nature of mathematical resilience, especially to establish its relationship with general resilience.